Construction of Narrative Issues of Immorality in Political Discourse : A Critical Study - Dothea Reanyaan; Ibrahim Kristofol Kendi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the construction of narratives on immoral issues in political discourse through a critical approach. Immoral issues are often used as political tools to build an image, discredit opponents, or divert public attention from the main issues. This study focuses on how immoral issues are designed, disseminated, and received by society through media and political discourse. Using critical discourse analysis, this research explores the relationship between power, ideology, and the representation of immoral issues in a political context. The findings show that immoral issues are frequently manipulated to influence public perception, control political narratives, and reinforce the dominance of certain groups. The implications of this practice include the distortion of public space, the decline in the quality of political discourse, and threats to democratic integrity. This study highlights the importance of critical literacy in political discourse to foster healthier and more substantive discussions.